Pengaruh Pemberian Ekstrak Temulawak (Curcuma Xanthorrizha Roxb.) Terhadap Level Nekrosis Pada Jaringan Lien Mencit Putih (Mus Musculus L.) Jantan Galur Balb/c yang Diinokulasi Plasmodium berghei ANKA - Muhammad Reyhan Arsya; Prawesty Diah Utami; Irmawati Dikman (Universitas Hang Tuah, 2019)
Abstract Background : Malaria is a disease caused by the Plasmodium, transmitted by Anopheles mosquito and is a health problem in Indonesia. Further development to find new innovations in malaria treatment. Purpose : to determine the effect of temulawak rhizome extract on the level of spleen necrosis of male mice inoculated with Plasmodium berghei ANKA. Methods : a post-test only control group design, used five groups. First group a normal mice, 2nd group was inoculated with Plasmodium berghei ANKA and three treatment groups were inoculated with Plasmodium berghei ANKA and treated with temulawak extract with a dose of 150 mg/KgBB (3rd group), 100 mg/KgBB (4rd group ), and 50 mg/KgBB (5rd group) for four day. On the fifth day observation of the level of spleen necrosis was examination by histopathological Result : the administration of ginger rhizome extract has an influence on the level of necrosis of male mice (Mus musculus L.) BALB / c inoculated with Plasmodium berghei ANKA α = 0,002 (ρ<0,05), where the administration of temulawak extract can increase necrosis levels compared to the control group . This is probably due to the lack of temulawak extract dosage and lack of observation in this study. Conclusion : extract Curcuma xanthorriza Roxb. Has an influence on the level of necrosis of male mice inoculated with Plasmodium berghei ANKA Keywords : Malaria, curcuma (Curcuma xanthorrhiza Roxb.), Necrosis level, Plasmodium berghei ANKA